Avaliação clinica e laboratorial de caes submetidos ao envenenamento por Tityus serrulatus, Lutz e Mello, 1992 (Scorpiones, Buthidae) - Eduardo Lara Ribeiro (2008)
Scorpion envenomation is an public health problem in Brazil. Clinical effects of scopion venom are well understood in humans and almost nothing in domestic animals. This study was undertaken to examine the deleterious effect of scorpion venom in dogs. Twelve healthy dogs were divided in two groups: GI (control) and GII (venom). Tityus serrulatus venom (250g/kg) diluted in 0,5ml PBS was given to GII by subcutaneous injection, in the left forearm, medial face. GI received 0,5ml of PBS. Dogs underwent clinical examination, with systemic cardiovascular parameters (electrocardiogram, echocardiogram, evaluation of arterial blood pressure and chest X-rays), blood profile, urinalysis, biochemical analysis such as levels of cortisol, insulin, CK, ALT, AST, LDH, cardiac troponin I (TnI), amylases, glucose, potassium, total protein and serum electrophoresis protein. Until 12h, GII showed behavioral changes, intense local pain, sneezing, salivation, vomiting, abdominal pain and lethargy. No major change was observed in echo and electrocardiography. Six hours after, GII displayed increased hematocrit values, leukocytosis with neuthrophilia and increases of ALT, AST, CK and glucose, without alterations in LDH, TnI, amylases, urea, creatinine, potassium and total protein levels. Only one dog presented glycosuria. Until 6h, increase in cortisol levels was observed in response to the pain, coinciding with the hyperglycemia and insulin elevations. Until 8h after, GII showed systolic blood pressure increased. In conclusion, this study showed that T. serrulatus venom may induce a variety of clinical symptoms in dogs